Cervantes's novel of modern times : a new reading of Don Quijote - Quint, David, 1950- (Princeton University Press, 2003)
"This book offers a radically new reading of Don Quijote, understanding it as a whole much greater than the sum of its famous parts. David Quint discovers a unified narrative and deliberate thematic design in a novel long taught as the very definition of the picaresque and as a rambling succession of individual episodes. Quint shows how repeated motifs and verbal details link the episodes, often in surprising and heretofore unnoticed ways. Don Quijote emerges as a work that charts and reflects upon the historical transition from feudalism to the modern times of a moneyed, commercial society." "A new and coherent guide through the mazelike structure of Don Quijote, this book invites readers to appreciate the perennial modernity of Cervantes's masterpiece - a novel that confronts times not so distant from our own."--Jacket